Layanan Perpustakaan Universitas Airlangga Berbasis Inklusi Sosial melalui Pembinaan UMKM di Wilayah Surabaya Utara dan Timur - Mutty Hariyati; Suhernik Suhernik; Agung Budi Kristiawan (Perpustakaan Nasional, 2022)
The social inclusion-based library transformation program initiated by the director of The National Library of the Republic of Indonesia serves as the background of the study. Libraries that prioritize social inclusion provide resources to the community to help them maximize their potential for welfare. The crucial and strategic function of Micro, Small and Medium Enterprises (MSME) is one of the factors contributing to Indonesia's economic growth. MSMEs and social inclusion-based libraries have a close working relationship since the community can develop imagination, innovation, and creativity in establishing and developing their products by library services. Airlangga University Library is one of the libraries founded on social inclusion and has been mentoring MSMEs in Surabaya's northern and eastern regions since 2019. The purpose of this study was to determine the role of sources of information, facilities and infrastructure as well as programs created by the Airlangga University Library in increasing the productivity and income of MSME actors. This is qualitative research using Focus Group Discussion (FGD) data collection technique. Interviews with 6 (six) assisted MSME actors showed that the programs created by the Airlangga University Library inspired them to be more enthusiastic about developing their businesses. The study's findings indicate that the library's programs can be used as a source of information for advancing and developing MSME. The Airlangga University Library is expected to provide more sources of information that are relevant to needs, infrastructure to market products and organize other programs that provide knowledge for MSME actors in developing business.